PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT KUNANGO JANTAN PEKANBARU - Mhd Fadli Waluyo; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is motivated by the importance of human resource management people in driving the company. To achieve the company’s goals, employees who have high job satisfaction are needed to anticipate the opportunities and challenges of an increasingly competitive business environtment. This research was conducted at PT Kunango Jantan Pekanbaru, located on Jl Raya Pekanbaru – Bangkinang, Rimba Panjang, Tambang District, Kampar Regency, Riau. The purpose of this study was to determine the level of job satisfaction of employees at PT Kunango Jantan Pekanbaru. The sample of this research was taken as many as 61 respondents using the random sampling method. In this research, the method used is descriptive and quantitative. The data obtained from the results of interviews and the distribution of questionaires/questionnaires were then statistically tested through the SPSS program. The analytical method used in this research is multiple linear regression analysis through validity and reliability test. In this study the result obtained are that organizational culture and work environtment have a positive effect on employee job satisfaction at PT Kunango Jantan Pekanbaru Keywords: Organizational Culture, Work Environment, Job Satisfaction PENDAHULUAN